Vivir la frontera desde las políticas públicas Juventudes preparatorianas de la Zona Metropolitana de Tijuana - Vargas Valencia, Fabiola Teresa (2022)
This article aims to analyze the impact of public policies on the welfare and development of high school youth in Baja California, Mexico, border with the United States of America. It proposes to respond around the situation of young people at the level of Higher Secondary Education, about their socioeconomic, political-cultural and rights opportunities, implemented by the neoliberal economic model during the period from the early 90s to the present. Specifically, three fundamental dimensions of city life are examined: 1) Urban spaces free from hostility and violence, 2) Right to education and 3) Right to work. Based on a case study, the educational institution CEC y TE Villa del Sol that belongs to the system of the College of Scientific and Technological Studies of the State of Baja California, documents the distribution and public management of the surrounding urban space, and the education policies and programs assumed by the institution during the 2017-2 school semester. This study concludes that in this area of metropolitan Tijuana, public policies have incurred in irregular procedures of weakening, to the point of sacrificing developing best practices in social interactions and with that the configuration of an organized system of youth settlement, social dynamics that affect the constitution of the city and citizenship.